2009
DOI: 10.1007/s00428-009-0827-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma with a high number of epithelioid histiocytes (lymphoepithelioid B-cell lymphoma): a study of Osaka Lymphoma Study Group

Abstract: The aim of this study was to clarify whether diffuse large B-cell lymphoma (DLBCL) with a high number of epithelioid histiocytes (DLBCL-EH) could have distinctive clinicopathological characteristics. Clinicopathological findings in 22 cases with DLBCL-EH and, as a control, 96 cases with ordinary type of DLBCL were analyzed. There were ten men and 12 women with ages ranging from 38 to 91 (median, 64) years. The primary site was lymph node in 16 cases, extranodal organs in three, and unknown in three. Stage of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Macrophages play an important role as one of the non‐neoplastic, inflammatory cells in tumour tissues, where they are termed tumour‐associated macrophages (TAMs). TAMs were reported to be associated with a worse prognosis in patients with follicular lymphoma 6 or classical Hodgkin’s lymphoma, 7 whereas we found that a high number of epithelioid histiocytes in DLBCL was correlated with a better prognosis 8 . In contrast, Hasselblom et al.…”
Section: Introductioncontrasting
confidence: 75%
“…Macrophages play an important role as one of the non‐neoplastic, inflammatory cells in tumour tissues, where they are termed tumour‐associated macrophages (TAMs). TAMs were reported to be associated with a worse prognosis in patients with follicular lymphoma 6 or classical Hodgkin’s lymphoma, 7 whereas we found that a high number of epithelioid histiocytes in DLBCL was correlated with a better prognosis 8 . In contrast, Hasselblom et al.…”
Section: Introductioncontrasting
confidence: 75%
“…Macrophages can play an important role in tumour tissues: they are termed tumour‐associated macrophages (TAMs). TAMs were reported to be associated with a worse prognosis in patients with follicular lymphoma 5 or classical Hodgkin’s lymphoma, 6 whereas we reported that a high number of epithelioid histiocytes in DLBCL was correlated with favourable prognosis 7 . In contrast, Hasselblom et al.…”
Section: Introductionmentioning
confidence: 59%
“…Extra-nodal non-Hodgkin's lymphomas (NHLs) account for about 24%-48% of all NHLs [ 5 ]. Extra-nodal NHLs involving only the epidural space account for 3.3% of all lymphomas, 9% of all the epidural spinal tumors, and 0.9% of all extra-nodal NHLs [ 6 ].…”
Section: Discussionmentioning
confidence: 99%